Equilibrium Evaluation of Active Labor Market Programmes Enhancing Matching Effectiveness - Bruno van der Linden (Institute for the Study of Labor (IZA), 2005)
This paper evaluates counselling programmes in an equilibrium matching model where workers are heterogeneous in skill levels. Job search effort, labour demand and wages are endogenous. When wages are bargained over, raising the effectiveness of or the access to counselling programmes pushes wages upwards and leads to lower search effort among nonparticipants. The effects of increasing the access of the low-skilled are evaluated numerically by enlarging successively the set of endogenous behaviours. Induced effects outweigh substantial positive micro effects on low-skilled employment when all `margins' are taken into account. The inter-temporal utility of the low-skilled nevertheless increases because search effort declines. On the contrary, when the net wage of the low-skilled is a fixed proportion of the one bargained by the high-skilled, raising the access to counselling programmes has small positive effects on all criteria.
Keywords: J65; J63; J64; J68; 330; active programmes; labour market policies; evaluation; equilibrium search